HUBUNGAN ANTARA IKLIM ORGANISASI DAN ETOS KERJA DENGAN KINERJA DOSEN AKADEMI KEPERAWATAN DI JAKARTA PUSAT - Roosmyaty Patras (Jurnal Manajemen Pendidikan, 2017)
The objective of this research is to study the relationship between organizational climate and work ethic with the lecture job performance. The study was conducted at Nursing Academy at Center Jakarta. This research using quantitative approach with survey method. Total samples using in this research 54 lectures that selected through simple random sampling. Data collecting using questionnaire with rating scale and data analysis with correlation and regression. The results of the research showed: Firtsly, there is a positive relationship between organizational climate with lecture job performance. Second, there is a positive relationship between work ethic with the lecture job perfrmance. Third, there is a positive relationship between organizational climate and work ethic simultaneously with the lecture job performance.